Animals may act as social buffers: Skin conductance arousal in children with autism spectrum disorder in a social context. Issue 5 (27th April 2015) - O'Haire, Marguerite E.; McKenzie, Samantha J.; Beck, Alan M.; Slaughter, Virginia
ABSTRACT Children with autism spectrum disorder (ASD) experience high rates of social stress and anxious arousal. Preliminary evidence suggests that companion animals can act as buffers against the adverse effects of social stress in adults. We measured continuous physiological arousal in children with ASD and typically developing (TD) children in a social context during four conditions: (a) a baseline of reading silently, (b) a scripted classroom activity involving reading aloud, (c) free play with peers and toys, and (d) free play with peers and animals (guinea pigs). Our results confirmed heightened arousal among children with ASD compared to TD children in all conditions, except when the animals were present. Children with ASD showed a 43% decrease in skin conductance responses during free play with peers in the presence of animals, compared to toys. Thus, animals may act as social buffers for children with ASD, conferring unique anxiolytic effects. © 2015 Wiley Periodicals, Inc. Dev Psychobiol 57: 584–595, 2015.